Implementing Problem-Based Learning to Improve Understanding of QS. Al Maun and Social Awareness - Riza Arfani; Ulul Albab (FITK UIN Walisongo Semarang, 2026)
This study aims to analyze the improvement of learning outcomes in Islamic Religious Education and Character Education (PAI and BP), specifically the material of QS. Al Maun and